Analysis of the Pleasure and the Reality Principles in Afghan Folk Tales and the Impact of Their Reading on Children - Turaan Mahmoodi, Abdulqadir (Journal of Social Sciences - Kabul University, 2025)
This study employs a descriptive–analytical approach based on qualitative content analysis. Its aim is to explore the representation of the psychoanalytic principles of pleasure and reality in Afghan folk tales and to examine their role in children’s psychological, moral, and social development. The significance of this research lies in presenting folk tales as educational and cultural tools that transmit moral values, internalize social norms, and convey psychological insights. The findings show that protagonists who endure hardships and adhere to the reality principle achieve success, reward, and lasting satisfaction, whereas characters driven by the pleasure principle, seeking comfort and immediate gratification, experience failure, suffering, and punishment. The results indicate that these tales, beyond their entertainment function, play a vital role in fostering realism, patience, adaptability, and cultural identity among children. Therefore, they can serve as effective educational and psychological resources in children’s upbringing and character formation.